Arab Republic of Egypt : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
The Arab Republic of Egypt's 2005 Article IV Consultation reports that the externally driven recovery has gained steam underpinned by a moderate revival in consumption and improved confidence. The Egyptian pound has appreciated, the stock market has reached record highs, and the current account surplus has increased, enabling banks and the Central Bank of Egypt to strengthen their net foreign asset position. The monetary policy did not contain inflation below double-digit rates, and government borrowing and debt remained high.